2013
DOI: 10.3389/fncom.2013.00127
|View full text |Cite
|
Sign up to set email alerts
|

From action representation to action execution: exploring the links between cognitive and biomechanical levels of motor control

Abstract: Along with superior performance, research indicates that expertise is associated with a number of mediating cognitive adaptations. To this extent, extensive practice is associated with the development of general and task-specific mental representations, which play an important role in the organization and control of action. Recently, new experimental methods have been developed, which allow for investigating the organization and structure of these representations, along with the functional structure of the mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 55 publications
7
45
0
Order By: Relevance
“…Our results corroborate findings from studies of complex movement representations (Bläsing et al, 2009; Güldenpenning et al, 2011, 2013; Weigelt et al, 2011; Land et al, 2013) and skill acquisition (Frank et al, 2013). They emphasize the role of cognitive representations and processes in action control and support the view that skill representations are based on categorical knowledge.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results corroborate findings from studies of complex movement representations (Bläsing et al, 2009; Güldenpenning et al, 2011, 2013; Weigelt et al, 2011; Land et al, 2013) and skill acquisition (Frank et al, 2013). They emphasize the role of cognitive representations and processes in action control and support the view that skill representations are based on categorical knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…They emphasize the role of cognitive representations and processes in action control and support the view that skill representations are based on categorical knowledge. In this regard, our study confirms the role of cognitive processes in the control of complex human actions as proposed in frameworks such as the ideomotor approach (Koch et al, 2004; for a histoical overview of the ideo-motor principle, see Stock and Stock, 2004), the theory of event coding (TEC; Hommel et al, 2001), or the cognitive action architecture approach (CAA-A; Schack and Ritter, 2009; Land et al, 2013). …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In numerous studies, mental representations of complex sport movements have been found to be dependent on expertise (e.g., Schack and Mechsner, 2006;Schütz et al, 2009;Land et al, 2013). In experts, the structure of such representations is more functional and more related to biomechanical principles than in novices.…”
Section: Introductionmentioning
confidence: 99%
“…The UE experiment used a whole body Vicon system model and 39 passive retro-reflective spherical body markers were positioned at specific anatomical skeletal places [12] on the surface of a special suit.…”
Section: Methodsmentioning
confidence: 99%